Relationship between ball impact location and joint angle changes for one-handed tennis backhand groundstrokes - King, M.; Hau, A.; Blenkinsop, G. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to investigate the effect of off-longitudinal axis and off-lateral axis ball-racket impact locations on racket and lower arm joint angle changes for one-handed tennis backhand ground strokes. Three-dimensional racket and wrist angular kinematic data were recorded for fourteen university tennis players. Off-longitudinal axis ball-racket impact locations explained over 70% of the variation in racket rotation about the longitudinal axis and wrist flexion / extension angles during the period immediately following impad. Off-lateral axis ball-racket impact locations had a less clear cut influence on racket and lower arm rotations. This study has confirmed that off-longitudinal impacts blow the longitudinal axis cause forced wrist flexion and established that there can be large differences in forced wrist flexion from individual to individual.